Chemical Composition, Antibacterial and Antioxidative Activities of Essential Oil from Ligularia pleurocaulis - Xie, Ya; Xie, Guang-Bo; Chen, Bing; Li, Sheng-Xiong; Tian, Jin (Asian Journal of Chemistry, 2014)
The genus Ligularia is known as folk medicine for their antibiotic, antiphlogistic and antitumor activities. The essential oil from the whole plant of Ligularia pleurocaulis was obtained by steam distillation and its chemical constituents were separated and identified by GC/MS. Antibacterial activities were evaluated by MTT colorimetric assay and antioxidative activity was screened spectrophotometrically through DPPH scavenging. Twenty seven compounds were identified from the essential oil, making up 81.94 % of the total contents. The essential oil showed moderate antibacterial activities against Escherichia coli and Staphylococcus aureus and weaker antibacterial activities against Bacillus subtilis. Meanwhile, its scavenging rate against DPPH was observed as 86.45 % in 40 mg/mL.